Case Report: Causative De novo Variants of KCNT2 for Developmental and Epileptic Encephalopathy - Gong, Pan; Jiao, Xianru; Yu, Dan; Yang, Zhixian (Frontiers in Genetics, 2021)
Objective KCNT2 gene mutations had been described to cause developmental and epileptic encephalopathies (DEEs). In this study, we presented the detailed clinical features and genetic analysis of two unrelated patients carrying two de novo variants in KCNT2 and reviewed eight different cases available in publications. Methods Likely pathogenic variants were identified by whole exome sequencing; clinical data of the patients were retrospectively collected and analyzed. Results Our two unrelated patients were diagnosed with Ohtahara syndrome followed by infantile spasms (IS) and possibly the epilepsy of infancy with migrating focal seizures (EIMFS) respectively. They both manifested dysmorphic features with hirsute arms, thick hair, prominent eyebrows, long and thick eyelashes, a broad nasal tip, and short and smooth philtrum. In the eight patients reported previously, two was diagnosed with IS carrying a ‘change-of-function’ mutation and a gain-of-function mutation respectively, two with EIMFS-like carrying a gain-of-function mutation and a loss-of-function mutation respectively, one with EIMFS carrying a loss-of-function mutation, three with DEE without functional analysis. Among them, two patients with gain-of-function mutations both exhibited dysmorphic features and presented epilepsy phenotype, which was similar to our patients. Conclusion Overall, the most common phenotypes associated with KCNT2 mutation were IS and EIMFS. Epilepsy phenotype associated with gain- and loss-of-function mutations could overlap. Additional KCNT2 cases will help to make genotype-phenotype correlations clearer.